2017
DOI: 10.1007/s10157-017-1477-7
|View full text |Cite
|
Sign up to set email alerts
|

A potentially crucial role of the PKD1 C-terminal tail in renal prognosis

Abstract: BackgroundAutosomal dominant polycystic disease (ADPKD) often results in renal failure. Recently, allelic influences of PKD1 mutation types on renal survival were extensively investigated. Here, we analyzed integrated influences of PKD1 mutation types and positions on renal survival.MethodsWe included 338 (82 pedigrees) and 72 (12 pedigrees) patients with PKD1 and PKD2 mutations, respectively, identified through comprehensive gene analysis of 101 probands with ADPKD. Genetic testing was performed using next-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Renal and extrarenal phenotypes of ADPKD are heterogeneous due to the varieties of PKD mutation types [13, 15, 16], modifying genetic factors [17], gender differences [18] and environmental factors [19]. Genetic, imaging, clinical, laboratory, and environmental predictors are factors that are related to determining ADPKD disease severity [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal and extrarenal phenotypes of ADPKD are heterogeneous due to the varieties of PKD mutation types [13, 15, 16], modifying genetic factors [17], gender differences [18] and environmental factors [19]. Genetic, imaging, clinical, laboratory, and environmental predictors are factors that are related to determining ADPKD disease severity [20].…”
Section: Discussionmentioning
confidence: 99%
“…The influences of PKD mutations types on AHTKV-α and measured HtTKV slopes were compared for 88 patients with previously characterized PKD mutations [13]. …”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported differences in renal prognosis by genotype [8][9][10][11][12][13]19]. The kidney survival rate depends on the causal genes (PKD1, PKD2) and differences between truncating or non-truncating mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney survival rate depends on the causal genes (PKD1, PKD2) and differences between truncating or non-truncating mutations. Patients with PKD1 mutations, particularly those with truncating mutations, show poor prognosis [8][9][10][11][12][13]19]. However, the relationship between differences in disease progression and mutation types, such as nonsense, frameshift, splicing mutation, and large deletions as truncating mutations, substitution, and in-frame deletion as non-truncating mutations, is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation